(untitled) (Journal of Shaheed Suhrawardy Medical College, 2018)
A patient having recurrent right sided lower abdominal pain was admitted as with appendicitis. Laparoscopic appendicectomy was done. On histopatholigical examination it was found to be Endometriosis. J Shaheed Suhrawardy Med Coll, December 2017, Vol.9(2); 83-84